Arrhythmias in Amateur Athletes: Warning Sign or Physiological Adaptation? - Twardowska, Daria; Śliwa, Wiktoria; Tłoczek, Wiktoria; Topolski, Kamil; Jelonek, Barbara; Wandzel, Małgorzata; Klubikowska, Karolina; Porada, Dagmara; Tomczak , Barbara; Wandasiewicz, Monika (Quality in Sport, 2026)
The prevalence of arrhythmias detected in physically active adults has increased in parallel with the growing participation of amateur athletes in endurance and high-intensity sports and with widespread use of wearable ECG-capable devices. Exercise training induces autonomic and structural cardiac remodeling that may manifest as bradyarrhythmias or ectopy and is frequently benign. However, long-standing high-volume endurance exercise has also been associated with a higher burden of atrial fibrillation and, in selected individuals, ventricular arrhythmias, raising the clinical challenge of distinguishing physiological “athlete’s heart” adaptations from arrhythmic phenotypes that may reflect underlying structural or electrical heart disease. This narrative review synthesizes current evidence regarding epidemiology, proposed mechanisms, ECG interpretation, diagnostic evaluation, detraining, management, and return-to-sport considerations for amateur athletes presenting with arrhythmias. Particular attention is given to atrial fibrillation, premature ventricular contractions, and ventricular tachyarrhythmias, as well as to the role of pre-participation evaluation and shared decision-making.